2012
DOI: 10.1103/physrevlett.108.158001
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of the Transition of Dune Shapes under a Unidirectional Wind

Abstract: A bifurcation analysis of dune shape transition is made. By use of a reduced model of dune morphodynamics, the Dune Skeleton model, we elucidate the transition mechanism between different shapes of dunes under unidirectional wind. It was found that the decrease in the total amount of sand in the system and/or the lateral sand flow shifts the stable state from a straight transverse dune to a wavy transverse dune through a pitchfork bifurcation. A further decrease causes wavy transverse dunes to shift into barch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Parteli et al [] have shown that a transverse dune is globally unstable because a difference in height accelerates the smallest longitudinal dune slice and is then amplified by lateral flows associated with avalanches. In our case, we show that when there is an input sand flux, the overall dispersive flux may be stronger on the windward face than on the lee face [ Niiya et al , ; Guignier et al , ]. This may be an important stabilizing factor which was not taken into account by Parteli et al [].…”
Section: Discussionmentioning
confidence: 62%
“…Parteli et al [] have shown that a transverse dune is globally unstable because a difference in height accelerates the smallest longitudinal dune slice and is then amplified by lateral flows associated with avalanches. In our case, we show that when there is an input sand flux, the overall dispersive flux may be stronger on the windward face than on the lee face [ Niiya et al , ; Guignier et al , ]. This may be an important stabilizing factor which was not taken into account by Parteli et al [].…”
Section: Discussionmentioning
confidence: 62%
“…The simulations of the genesis of barchan fields were discussed in detail in previous works (Durán et al, 2010;Luna et al, 2011Luna et al, , 2012. As shown in these works, the small transverse bedforms emerging from the instabilities which develop on the flat hill upwind give place to small barchans after reaching the bedrock -due to the cross-wind instability inherent to transverse dunes (Reffet et al, 2010;Parteli et al, 2011;Melo et al, 2012;Niiya et al, 2012). The barchan dunes, which are subjected to a strong influx, grow in size during their migration, thereby experiencing multiple collisions with their counterparts and producing complex, asymmetric dune shapes.…”
Section: Dune Collisionsmentioning
confidence: 97%
“…However, it is worth recalling that transverse dunes can decay into a chain of barchans (crescent-shaped dunes) and display a "sea-wave-like" shape with meandering. The formation of barchan dunes is very common and widely studied in an aeolian environment, as demonstrated by a vast body of literature [9][10][11], but has also been detected in subaqueous conditions both in laboratory experiments [12] and in real rivers [13].…”
Section: Introductionmentioning
confidence: 99%